1988
DOI: 10.1902/jop.1988.59.4.259
|View full text |Cite
|
Sign up to set email alerts
|

Intragingival Occurrence of Actinobacillus actinomycetemcomitans and Bacteroides gingivalis in Active Destructive Periodontal Lesions

Abstract: A total of six active and six nonactive sites from six untreated periodontitis patients were examined for intragingival presence of Actinobacillus actinomycetemcomitans and Bacteroides gingivalis. The active destructive periodontal disease was determined by the "tolerance method." The method of immunoperoxidase was used in the identification of intragingival microorganisms in active and nonactive periodontal sites. Light microscopic sections of gingival tissues consecutive to those with gram stain, revealing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
104
1
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(113 citation statements)
references
References 8 publications
6
104
1
2
Order By: Relevance
“…The data support the view that the NF-B signaling cascade is a component in the CD99-mediated adhesion response. In recent years gingipains have been associated with the ability to destroy epithelial barriers and infiltrate vascularized periodontal tissues (3,17,34). In line with these findings, the results of the present study support a role for gingipains in down-regulation of CD99 expressed on endothelial junctions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The data support the view that the NF-B signaling cascade is a component in the CD99-mediated adhesion response. In recent years gingipains have been associated with the ability to destroy epithelial barriers and infiltrate vascularized periodontal tissues (3,17,34). In line with these findings, the results of the present study support a role for gingipains in down-regulation of CD99 expressed on endothelial junctions.…”
Section: Discussionsupporting
confidence: 90%
“…Among periodontopathogens, most evidence points to a pathogenic role for Porphyromonas gingivalis, which is more frequently detected in active lesions of periodontitis than in healthy or gingivitis sites (37,38). Previous studies have shown that P. gingivalis may penetrate the epithelial barrier surrounding the gingival sulcus and invade endothelial cells (3,17,34). Virulence of P. gingivalis is associated with the proteolytic enzymes expressed by this gram-negative anaerobic bacterium (21,24).…”
mentioning
confidence: 99%
“…Further, P. gingivalis has been observed within gingival tissues in vivo (55), whereas tissue penetration and destruction by P. gingivalis have been demonstrated in vitro (1). These results indicated that P. gingivalis may invade deeper structures of the connective tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the gram-negative anaerobic bacterium Porphyromonas gingivalis has been implicated to be one of the major etiological agents of chronic adult periodontitis. P. gingivalis colonizes in periodontal pockets and spreads into deeper tissues, including connective and bone tissues (11,14,21,22,25,40,47). The bacterium possesses a number of virulence factors, such as fimbriae, lipopolysaccharide (LPS), and cysteine proteinases named gingipains (11,21).…”
mentioning
confidence: 99%